KERJASAMA PEMERINTAH PROVINSI RIAU DAN BNN PROVINSI RIAU DALAM UPAYA PENCEGAHAN, PEMBERANTASAN, PENYALAHGUNAAN DAN PEREDARAN GELAP NARKOBA (P4GN) DI LINGKUNGAN PEMERINTAH PROVINSI RIAU TAHUN 2019 - Aldi Sofiandi; Adlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Combating narcotics in society is one of the roles and responsibilities of the Indonesian government at both the national and regional levels. The danger of narcotics abuse has become a serious phenomenon that must be addressed and resolved by both the Government, the authorized apparatus and with all elements of society. In order not to have too many victims of the dangers of narcotics, serious countermeasures are held by carrying out repressive and preventive actions simultaneously and are directed and continuous. The formulation of the problem in this research is How the Cooperation between the Riau Provincial Government and the National Anti Narcotics Agency of Riau in efforts to prevent, eradicate, abuse and illicit drug trafficking in the Riau Provincial Government in 2019 and what are the inhibiting factors in the Cooperation between the Riau Provincial Government and the National Anti Narcotics Agency of Riau in efforts to prevent, eradicate, abuse and illicit drug trafficking in the Riau Provincial Government in 2019.The purpose of this study is to determine the cooperation between the Riau Provincial Government and the National Anti Narcotics Agency of Riau in efforts to prevent, eradicate, abuse and illicit drug trafficking in the Riau Provincial Government in 2019 and to describe the inhibiting factors in the Cooperation between the Riau Provincial Government and the National Anti Narcotics Agency of Riau in efforts to prevent, eradicate, abuse and illicit drug trafficking in the Riau Provincial Government in 2019. The results of this study are to find out how the cooperation of the Riau Provincial Government and the National Anti Narcotics Agency of Riau in Efforts to Prevent, Eradicate, Abuse and Illicit Drugs (P4GN) in the Riau Provincial Government Environment in 2019 through indicators of Consortia, Cooperative Construction, Joint Service and Other Arrangements. The factors that hinder in preventing narcotics abuse in Pekanbaru City are the weak legal or constitutional system in Indonesia, weak law enforcement by law enforcement agencies, the factor of low awareness of Riau Provincial Government employees and the cultural factors of the community who do not care about narcotics abuse in the city. Pekanbaru. Keywords: Coordination, Cooperation, Prevention, Eradication, Abuse of Illicit Drug Trafficking (P4GN)